Connective tissue responses to calcium hydroxide-based root canal medicaments - Nelson Filho, P.; Bezerra Silva, L. A.; Leonardo, M. R. [UNESP]; Sabbag Utrilla, L. [UNESP]; Figueiredo, F. (Wiley, 1999)
Aim: The objective of the present study was to evaluate the tissue inflammatory response induced by calcium hydroxide pastes, with or without paramonochlorophenol and camphor. Methodology: Isogenic BALB/c mice were inoculated into the subcutaneous tissue with either 0.1 mL of a suspension of Calen, Calen with camphorated paramonochlorophenol, Calen with paramonochlorophenol, Calasept paste or phosphate-buffered saline (control). After 6, 12 and 24 h and 2, 3, 5, 7 and 15 days, three animals in each group were sacrificed and the excised lesions processed for histopathological evaluation of the inflammatory response. Events monitored and graded included the assessment of vascular congestion, oedema, haemorrhage, inflammatory infiltrate, necrosis and tissue repair. Results: The pastes induced an inflammatory response at every observation period, although the intensity, duration and extension of inflammation varied. Calen paste always produced an initial short-term inflammatory response whilst the other pastes produced extended reactions. All pastes allowed repair to take place by the end of the experimental period, although the speed of this process varied between the materials. Calen presented the best biocompatibility; the phenolic compound caused greater tissue response, which was even more severe in the absence of camphor. Calasept paste was damaging and the repair process slower. Conclusions: All calcium hydroxide formulations caused an inflammatory response. The severity and longevity of the responses varied between pastes as a result of the various antiseptic agents. Although irritating, repair was apparent with all formulations.
Keywords: Antibacterial dressing; Biocompatibility; Calcium hydroxide